2020
DOI: 10.1186/s13054-020-03200-1
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and encephalopathy in severe COVID-19: a cohort analysis of ICU patients

Abstract: Background Neurotropism of SARS-CoV-2 and its neurological manifestations have now been confirmed. We aimed at describing delirium and neurological symptoms of COVID-19 in ICU patients. Methods We conducted a bicentric cohort study in two French ICUs of Strasbourg University Hospital. All the 150 patients referred for acute respiratory distress syndrome due to SARS-CoV-2 between March 3 and May 5, 2020, were included at their admission. Ten patients (6.7%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
339
4
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(384 citation statements)
references
References 38 publications
22
339
4
19
Order By: Relevance
“…4 Our sparse data on cerebrospinal fluid suggest that increased blood-brain barrier permeability may contribute to neurological symptoms, as previously described for mild central nervous system inflammation in ICU patients. 1 In conclusion, pattern of cognitive deficits, present during the acute stage in our 13 patients without history of cognitive, psychiatric or neurological disorders, is probably linked to critical illness as part of ARDS due to COVID-19, since it is very similar to those reported in ARDS of other aetiologies. Further investigations are needed to determine predictive factors and underlying neural mechanisms, and clarify with a longterm follow-up whether patients will completely recover.…”
Section: Lettersupporting
confidence: 66%
See 1 more Smart Citation
“…4 Our sparse data on cerebrospinal fluid suggest that increased blood-brain barrier permeability may contribute to neurological symptoms, as previously described for mild central nervous system inflammation in ICU patients. 1 In conclusion, pattern of cognitive deficits, present during the acute stage in our 13 patients without history of cognitive, psychiatric or neurological disorders, is probably linked to critical illness as part of ARDS due to COVID-19, since it is very similar to those reported in ARDS of other aetiologies. Further investigations are needed to determine predictive factors and underlying neural mechanisms, and clarify with a longterm follow-up whether patients will completely recover.…”
Section: Lettersupporting
confidence: 66%
“…However, the occurrence of ICU delirium tends to be associated with poorer cognitive performance. 1 Structural damage, such as ischaemic or hypoxemic lesions of the hippocampus, basal ganglia or cerebellum lesions as well as brain atrophy (in particular hippocampal) or disruption of functional connectivity, which occur frequently in ARDS survivors, 3 4 may contribute to cognitive dysfunction. In the context of COVID-19, stroke and perfusion abnormalities have been reported, 1 2 but were excluded here in all 11 patients, who had brain imaging during the acute stage.…”
Section: Pattern Of Cognitive Deficits In Severe Covid-19mentioning
confidence: 99%
“…The incidence of delirium in COVID-19 has been reported to range from 9 [51] to 14.8% [40], which is 1.5-twofold lower than the prevalence rate reported in two recent systematic reviews and meta-analyses for adults either treated in an intensive care unit (ICU) in general [58], or due to COVID-19 infection (64% [18]) on neurology wards (27% [59]) or those requiring end-of-life care/symptom control (24% [60]). Similarly, a bicentre French study reported very high incidence of delirium in their severely ill COVID-19 patents in the ICU [118/140 (84.3%)], with 88 patients (69.3%) exhibiting hyperactive delirium, despite high infusion rates of sedative treatments and neuroleptics [61]. The Brain MRI performed in 28 patients demonstrated enhancement of subarachnoid spaces in 17/28 patients (60.7%), intraparenchymal, predominantly white matter abnormalities in 8 patients, and perfusion abnormalities in 17/26 patients (65.4%).…”
Section: Delirium In Covid-19mentioning
confidence: 90%
“…Cerebrospinal fluid examination revealed inflammatory disturbances in 18/28 patients, including oligoclonal bands with mirror pattern and elevated IL-6. The CSF RT-PCR SARS-CoV-2 was positive in one patient [61].…”
Section: Delirium In Covid-19mentioning
confidence: 96%
“…Elevated IL-6 and abnormal permeability of blood meningeal barrier associated with encephalopathy was identified in another cohort with 140 patients admitted to ICU with COVID-19 diagnosis. Eighty-four percent showed abnormal neurological examination and/or delirium with significant worse prognosis compared to patients without delirium and normal neurological exam (Helms et al, 2020b). It might be explained by the intense systemic inflammatory response that leads to blood-brain barrier leakage and higher permeability to peripheral cytokines that exacerbate neuroinflammation and consequently, neurological damage (Cain et al, 2019).…”
Section: Sars-cov-2 and The Central Nervous Systemmentioning
confidence: 99%